Inhalation Forms of Ambroxol in the Therapy of Respiratory Tract Secretory-Evacuation Disorders in Acute Bronchitis in Children - L.S. Ovcharenko; A.A. Vertegel; T.G. Andriyenko; N.V. Zhikhareva; I.V. Samokhin; V.Yu. Tkachenko (Zaslavsky O.Yu., 2014)
The mucoactive therapy of children aged 1 to 5 years with acute bronchitis using drug Lasolvan solution for oral and inhalation use or syrup for oral use Lasolvan is highly effective and safe method for management of respiratory tract secretory-evacuation disorders. Given the chance of inhalation therapy, effective treatment of choice, while maintaining a high safety profile, is inhalation of Lasolvan solution for oral and inhalation use by nebulizer. More rapid decline in the clinical severity of acute bronchitis in children treated with inhaled Lasolvan associated with accelerated recovery of disturbed secretory-evacuation mechanisms of bronchial tree.